The use of multiple linear regression technology in controlling the technical specifications of industrial products (predicting the mechanical specifications of the products of the longitudinal rolling factory of the Libyan Iron and Steel Company) - Azouza, Omar; Naser, Madi (Journal of Pure & Applied Sciences, 2021)
The main objective of this study is to arrive at the formulation of a model through which to predict the mechanical specifications of the products of the longitudinal rolling mill of the Libyan Iron and Steel Company, using the multiple linear regression method, and in a simple, accurate manner through which the quality of the products can be controlled within the specifications approved by the Libyan Iron and Steel Company Given the proportions of the added chemicals, the mechanical specifications of the products were predicted from yield stress, tensile strength and elongation ratio, and the error rate in predicting these mechanical specifications was very close to zero. This research also contributes to introducing the Libyan Iron and Steel Company to the importance of prediction models for mechanical properties, which work to reduce the rate of uncertainty, especially with the development of forecasting methods that allow improving the degree of accuracy and help in making sound decisions.